Toxic elements and microbial loads in african giant land snail (Archachatina margenata) reared with waste contaminated soil (Applied Research in Science and Technology, 2021)
The use of dump soils for the rearing of African giant land snail (AGLS) leads to the bioaccumulation of metals and microbial loads in AGLS, which is a major food chain route for the human body. This study investigated the concentrations of heavy metals (As, Cd, Cr, Hg, and Pb) and microbial load in AGLS reared with dumpsite and control soil and also to ascertain if they are within permissible limits. Soil samples; dump soil (A), and Control soil (B) were collected at 0-30 cm depth with the aid of a soil auger and were used for AGLS farming, to ascertain whether the Toxic elements (TEs) concentration was within the permissible limits on AGLS consumption. A total of 18 juvenile snails of similar weights was used for the study. The experiment lasted for three months (90 days), during which the snails were subjected to similar dietary reign and equal quantity of feed. The soil samples were analyzed for TEs before and after farming, and a snail was also analyzed for TEs after farming using an atomic absorptions spectrophotometer (AAS). Standard methods of APHA were used to determine microbial loads such as Total heterotrophic bacteria, E. coli, total coliform, fecal coliform, Staphylococcus aureus, Salmonella, and intestinal parasites. Results indicated that bacterial counts recorded in this study exceeded the recommended levels by WHO and ICMSF, standards (i.e. 10 to 102 coliforms g-1, 10 fecal coliform g-1, and 4.9×106 aerobic count g-1). The result shows a significant difference (P<0.05) between the dump and the control soil The concentration of TEs (As, Cd, Cr, Hg, and Pb) in snails reared with dump soil were 2.20, 2.68, 1.08, 2.23, and 2.89 mg/kg respectively. The control recorded 0.28, 1.89, 0.36, 0.16 and 0.24 mg/kg. The values were greater than the maximum permissible limit of 0.5, 2.0, 0.3, 0.1, and 0.1 mg/kg respectively recommended by FAO/WHO compared to the control. The study concludes that snails bioaccumulate toxic elements and microbial loads from the soil used in rearing them which is deleterious to human health when consumed.